Why has Computer Assisted Learning made so little impact in secondary education? Lessons from an economics and business subject case-study - Hurd, Steve (Curriculum journal (London, England), 2009)
This article reports the findings and draws lessons from a major twenty-year longitudinal study of computer use in economics and business studies teaching in UK secondary schools. Over the period, the level and pattern of computer use within subject lessons has changed substantially. In particular, there has been a progressive shift away from enquiry-based applications, associated with the Computer Assisted Learning (CAL) genre of software, in favour of generic applications. Various factors within the school and the wider educational environment have contributed to the observed changes, including teachers' continuing lack of confidence with ICT, the collapse of the educational software market and the increasingly competitive nature of schools. The result has been a virtual halving of computer use within mainstream lessons over the past decade. The article concludes that perhaps the time has arrived to take a more even-handed approach towards different learning resources and approaches.